Malaria parasites of long-tailed macaques in Sarawak, Malaysian Borneo: a novel species and demographic and evolutionary histories - Thamayanthi Nada Raja; Ting Huey Hu; Ramlah Zainudin; Kim Sung Lee; Susan L. Perkins; Balbir Singh (BMC Evolutionary Biology, 2018)
Abstract Background Non-human primates have long been identified to harbour different species of Plasmodium. Long-tailed macaques (Macaca fascicularis), in particular, are reservoirs for P. knowlesi, P. inui, P. cynomolgi, P. coatneyi and P. fieldi. A previous study conducted in Sarawak, Malaysian Borneo, however revealed that long-tailed macaques could potentially harbour novel species of Plasmodium based on sequences of small subunit ribosomal RNA and circumsporozoite genes. To further validate this finding, the mitochondrial genome and the apicoplast caseinolytic protease M genes of Plasmodium spp. were sequenced from 43 long-tailed macaque blood samples. Results Apart from several named species of malaria parasites, long-tailed macaques were found to be potentially infected with novel species of Plasmodium, namely one we refer to as “P. inui-like.” This group of parasites bifurcated into two monophyletic clades indicating the presence of two distinct sub-populations. Further analyses, which relied on the assumption of strict co-phylogeny between hosts and parasites, estimated a population expansion event of between 150,000 to 250,000 years before present of one of these sub-populations that preceded that of the expansion of P. knowlesi. Furthermore, both sub-populations were found to have diverged from a common ancestor of P. inui approximately 1.5 million years ago. In addition, the phylogenetic analyses also demonstrated that long-tailed macaques are new hosts for P. simiovale. Conclusions Malaria infections of long-tailed macaques of Sarawak, Malaysian Borneo are complex and include a novel species of Plasmodium that is phylogenetically distinct from P. inui. These macaques are new natural hosts of P. simiovale, a species previously described only in toque monkeys (Macaca sinica) in Sri Lanka. The results suggest that ecological factors could affect the evolution of malaria parasites.